Humoral immune response to Q fever vaccination of three sheep flocks naturally pre-infected with Coxiella burnetii. Issue 10 (5th March 2021) - Bauer, Benjamin U.; Knittler, Michael R.; Prüfer, T. Louise; Wolf, Annika; Matthiesen, Svea; Runge, Martin; Ganter, Martin
Highlights: Coxiella burnetii phase I vaccine induces an IgG phase II antibody response in sheep. IgG phase I C. burnetii antibodies last long in pre-infected sheep after vaccination. Phase-specific ELISAs recognize more seropositive sheep than the blended ELISA. Abstract: Q fever is a zoonotic disease caused by the bacterium Coxiella burnetii ; Coxiella -infected ruminants are the main reservoir shedding the pathogen during abortion or parturition through birth products. Germany has a long history of small-scale Q fever epidemics in the human population mostly associated with lambing sheep. Therefore, fast and efficient control measures are essentially required to prevent transmission from infected sheep flocks to humans. In our present study, three sheep flocks were vaccinated with an inactivated C. burnetii phase I vaccine after a field infection with C. burnetii was diagnosed. Serum samples and vaginal swabs were collected at different time points to evaluate the extent of the outbreak and the consequences of the vaccination. The serum samples were examined by phase-specific IgG phase I and phase II ELISAs and a commercial ELISA, simultaneously detecting both phase variations. Moreover, vaginal swabs were analysed by qPCR. The fourth flock with no Q fever history and non-vaccinated animals were used as a control group to evaluate the phase-specific ELISAs. The inactivated C. burnetii phase I vaccine induced an IgG phase II response and boosted the humoral immune reaction against natural pre-infections. Furthermore, the longevity of vaccine-induced antibodies seems to depend on previous infections. Around 16 months after primary vaccination, mainly IgG phase I antibodies were detectable. Vaccination did not prevent shedding at the next lambing season. Most interestingly, the phase-specific ELISAs revealed more C. burnetii positive animals than the blended ELISA-Assay. Taken together, phase-specific ELISAs are suitable tools to provide insights into natural- or vaccine-induced humoral immune responses to C. burnetii in sheep.